Choosing trash instead of nature: Sea urchin covering behavior. (June 2020) - Barros, Francisco; Santos, Daniel; Reis, Alice; Martins, Amanda; Dodonov, Pavel; Nunes, José Anchieta C.C.
Abstract: Notwithstanding impacts of marine debris on fauna by ingestion and suffocation, little is known about debris-related behavior. Lytechinus variegatus is a common sea urchin known for its covering behavior. We hypothesized that L. variegatus would select more marine debris (i.e. litter) than natural material as cover and we also expected that the selected natural and artificial material would be different in weight, sizes and transparency. We haphazardly collected marine debris and natural material on 20 individuals of L. variegatus and on the bottom, around each individual. All sampled material was weighed, measured and classified regarding opacity, nature (natural or artificial). Our results showed that i) sea urchins picked more litter than natural objects, ii) proportional weight of litter carried by urchins was significantly larger than expected by chance, iii) when considering all objects (on urchins and on the bottom) litter was heavier, wider and less opaque than natural material and iv) litter carried by the urchins were wider and less opaque than natural material. We suggest that litter can influence urchin's protection against sunlight, camouflage and ballast and that sea urchins with covering behavior might be used as indicators of marine debris in coastal and deep waters. Graphical abstract: Unlabelled Image Highlights: Little is known about impact of debris on fauna behavior. Lytechinus variegatus is a common sea urchin known for its covering behavior. Urchins picked more litter than natural objects and litter on urchins were wider and less opaque. Litter may influence urchin's protection against sunlight, camouflage and ballast. Urchins with covering behavior might be used as indicators of marine debris in coastal and deep waters.